Healthcare Quality and Dementia Risk - José M. Aravena; Xi Chen; Becca R. Levy (Global Labor Organization (GLO), 2024)
Low healthcare quality has been found to predict the development of several illnesses in older adults, while the evidence on dementia is still lacking. This study assesses whether and to what extent experiencing low healthcare quality can be associated with developing dementia in people 60-years-old and greater. Participants in the Health and Retirement Study (HRS), without dementia and 60-years-old and greater at baseline, were followed 2006 through 2019. Experiencing low healthcare quality was assessed at baseline through healthcare discrimination and dissatisfaction with healthcare services. The outcome, development of new cases of dementia, was determined through physician diagnosis or a cognition score compatible with dementia (assessed by the Telephone Interview for Cognitive Status). Cox regression is used to estimate the hazard ratio (HR) of dementia, adjusting for participants' demographic, health, and socioeconomic factors. Experiencing low healthcare quality is associated with increased dementia risk over 12 years (unadjusted HR: 1.68, 95%CI: 1.27 - 2.21, p-value< 0.001; fully adjusted HR: 1.50, 95%CI: 1.12 - 2.01, p-value: 0.006). Healthcare discrimination and dissatisfaction with the healthcare quality received are independently associated with increased dementia risk. To date, most measures to reduce dementia have focused on individual-level behaviors. Our findings suggest that implementing structural changes to improve healthcare quality delivery for older persons may reduce dementia prevalence.
Keywords: I11; I18; J14; J15; J18; 330; Dementia; Patient Satisfaction; Perceived Discrimination; Social Determinants of Health; Healthcare Quality; Alzheimer's Disease